Management of Water Hyacinth (Eichhornia Crassipes(MArt.)Solms)Using Fungul Pathogens - Praveena R (Department of Plant Pathology, College of Agriculture, 2003)
The study entitled "Management of water hyacinth using fungal pathogens" was conducted in College of Agriculture, Vellayani, Thiruvananthapuram during 1999-2002 period. A survey was carried out for a period of one year at quarterly intervals in four southern districts of Kerala to isolate fungi infecting water hyacinth. Myrothecium advena was the most commonly seen fungus followed by Fusarium pallidoroseum irrespective of the season. A positive correlation between the occurrence of fungi and maximum temperature, relative humidity, total rainfall and number of rainy days and negative correlation with maximum temperature was observed. Out of the 21 fungi tested for pathogenicity, 17 were found to be pathogenic on water hyacinth. Only M. advena (61.11 %) and F. pallidoros eum (53.44 per cent) caused more than 50% infection. The Fusaria, Alternaria and Myrothecium isolated from water hyacinth were identified as F. oxysporum, F. pallidoroseum, F. moniliformae, A. eichhorniae and M advena, of which M. advena was a new report on water hyacinth. Host range of M. advena, F. pallidoroseum, F. equiseti and C. gloeosporioides were studied. M. advena infected 27 cultivated and 45 weed plants, while F. pallidoroseum was limited to six cultivated and 20 weed plants. Cell free metabolites of M. advena produced maximum damage of 97.75 per cent on water hyacinth followed by metabolites of F. pallidoroseum (48.84 per cent). The cell free culture filtrate of M. advena could produce